Relationships between body build and knee joint flexor and extensor torque of Polish first-division soccer players - Pietraszewska, J.; Struzik, A.; Burdukiewicz, A.; Stachon, A.; Pietraszewski, B. (Applied Sciences, 2020)
Featured Application: Body height, body mass and thigh and calf girths are the anthropometric variables that best describe the values of the torque of the knee flexors and extensors that can be achieved by soccer players. Based on these anthropometric variables, the coach can initially assess players` strength abilities, which can help plan individual training programmes. Abstract: The aim of the study is to identify the relationships between anthropometric variables and knee joint extensor peak torque, knee joint flexor peak torque, and conventional hamstring-to-quadriceps ratio in Polish first-division soccer players. The study examined 37 soccer players aged 19 to 30 years (body mass: 76.8 7.2 kg, body height 1.82 0.06 m). Muscle torques of the knee joint were measured under isometric conditions using a Biodex 4 Pro dynamometer. The anthropometric variables such as body part lengths, breadths, and girths and skinfold thickness were measured. The strongest relationships of knee joint extensors were observed with body mass and variables describing skeleton size and lower-limb muscles. Regarding knee flexor torque, a significant relationship was found only with body mass. However, no significant relationships were observed between the conventional hamstring-to-quadriceps ratio and the anthropometric variables studied. The regression analysis results identified body height, body mass, and thigh and calf girth as the features most associated with knee joint torque. However, anthropometric measurements do not provide full information about the torque proportions of antagonist muscle groups, which is very important for injury prevention. Therefore, measurements using special biomechanical equipment are also necessary for the comprehensive analyses and control of the e ects of sports training.